Enhanced External Counterpulsation in Chronic Heart Failure: Where Do We Stand? - Ryan Ranitya (Interna Publishing, 2015)
Heart failure has been known as an increasing health burden worldwide and the prevalence is expected to rise more than 23 million in 2030. Chronic heart failure has characteristic of ventricular dysfunction which will cause dyspnea, fatique, and finally some limitation in functional capacity and reduced quality of life. Recent advances in treatment of chronic heart failure may give us option of wide variety of modalities from pharmacologic and nonpharmacologic therapy with invasive and noninvasive approaches. Each has its own benefit and risk. Structural heart disease of heart failure indicates non reversible damage. Thus, treatment will aim to prevent symptoms and improve quality of life. Enhanced external counterpulsation (EECP) was a non-invasive treatment originally to reduce symptom of refractory angina.2-4 In the newest European Society of Cardiology (ESC) guideline for management of stable coronary artery disease 2013, EECP had been approved as class IIa-recommended treatment for refractory angina.